1976
DOI: 10.1002/1097-0142(197601)37:1<220::aid-cncr2820370132>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitive reactions and antibody formation during L-asparaginase treatment of children and adults with acute leukemia

Abstract: One hundred and fourteen patients with acute leukemia, 57 children (10 AML and 47 ALL) and 57 adults (37 AML and 20 ALL) were treated with L-asparaginase (Asnase) 200 or 1000 IU/kg daily for 30 days unless withdrawn on account of side effects. Combinations with other cytotoxic drugs were used in all but eight patients. Hypersensitive reactions, decrease in Asnase activity in plasma, and bivalent antibodies to Asnase appeared more frequently in adults (28%, 46%, and 79%, respectively) than in children (16%, 17%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
75
0
5

Year Published

1979
1979
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 13 publications
1
75
0
5
Order By: Relevance
“…Antiasparaginase antibodies have been associated with increased drug clearance thus shortening its half-life, 8,9 decreasing circulating enzyme activity, 10,11 or lowering enzyme activity by deposition of antigen-antibody complex in the reticuloendothelial system. 12 Asparaginase-specific IgG antibodies appear to correlate with clinical allergic reactions. 13,14 The severity of hypersensitivity reactions to the three asparaginase preparations ranges from mild allergic reactions to anaphylactic shock.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiasparaginase antibodies have been associated with increased drug clearance thus shortening its half-life, 8,9 decreasing circulating enzyme activity, 10,11 or lowering enzyme activity by deposition of antigen-antibody complex in the reticuloendothelial system. 12 Asparaginase-specific IgG antibodies appear to correlate with clinical allergic reactions. 13,14 The severity of hypersensitivity reactions to the three asparaginase preparations ranges from mild allergic reactions to anaphylactic shock.…”
Section: Introductionmentioning
confidence: 99%
“…18,22 Recently, the importance of 'silent hypersensitivity' has been recognized in patients who developed antiasparaginase antibodies without clinical evidence of a hypersensitivity reaction. 6,9,12,21 Investigators found that those patients had a significant reduction in plasma asparaginase activity 9 and suboptimal asparagine depletion. 23 Allergic reactions to one preparation can be circumvented in most patients by the substitution to another preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-asparaginase antibodies occur in as many as 70% of children receiving E. coli asparaginase. 3,[10][11][12] The best course of action, including the use of premedications and substitution with PEG, or Erwinia asparaginase, in cases with frank or silent hypersensitivity to E. coli asparaginase, is also not clear.…”
Section: Introductionmentioning
confidence: 99%
“…9 It has been suggested that development of antibodies may hamper the antileukemic effect of asparaginase by shortening its half-life, preventing or delaying absorption after intramuscular injection, or interfering with enzyme activity. 3,10,11 The reported frequency of anti-asparaginase antibodies is quite variable, and so high in some subgroups of patients (ie over 70% in adults receiving E. coli asparaginase) 10,12 that it is not clear whether antibody levels are more frequently detected or higher in patients who exhibit overt clinical allergy than in identically treated patients without clinical evidence of hypersensitivity. Therefore, the objective of this study was to retrospectively compare anti-asparaginase antibody concentrations at identical time points relative to therapy in ALL patients who did and who did not develop hypersensitivity reactions to asparaginase.…”
Section: Introductionmentioning
confidence: 99%